Investigating the role of urban spaces in reduction of digital divide between citizens - Babaei, Ahoora; Bayzidi, Qader (Kurdistan Journal of Applied Research, 2017)
The information and communication technologies and their ever expanding and development have transformed all the basic concepts of human life, including the collective life of humans in urban spaces. Now these technologies have caused gradual and sometimes sudden changes in the concepts of space, so that, along with urban spaces, we are witnessing the creation of virtual environments with a wide variety of inclusive activities. This phenomenon led to the formation of virtual communities with a metropolitan state and the virtual universe formation in parallel with the real world. One of the implications of dual spatial and globalization for life of human beings is the creation of a crisis called the digital divide, which is associated with individualism, the reduction of social interactions levels, reducing collective life in the city's social spaces. The present study is carried out aimed to explain the role and capabilities of urban spaces on reducing the individuality of the crisis and promoting interactive levels and social integration. For this purpose, in the research process, three methods of environmental mapping, observation of behavior and interview with users in the Bam-e Tehran Recreational Complex have been used. The results showed that cyberspace is not considered as a substitute for physical space and serves as a complement to complete the social functions of urban spaces. Therefore, the creation of smart environments in this urban space and the creation of a hybrid space of physical and cyberspace, called the cyber park, will lead to an ever-increasing active presence of citizens and the promotion of levels of social interaction and ultimately reduce the digital divide among citizens.